Comparative assessment of dental anxiety among dental and pharmacy students in Paonta Sahib, Himachal Pradesh - Sumeet Bhatt; Ambika Gaur (Wolters Kluwer Medknow Publications, 2019)
Background: Dental anxiety is a recognized problem for both patients and dental professionals. The data on dental anxiety of professional students in India are limited. It has been suggested that repeated exposure to dental treatment environment could result in lowering of dental anxiety. Aim: The aim of this study was to compare the self-reported levels of dental anxiety among dental and pharmacy students at an Indian institute. Materials and Methods: A total of 437 students of dentistry and pharmacy participated in the study. Dental anxiety of the students was assessed using the Modified Dental Anxiety Scale. Data on demographic details and previous dental experience were also collected using a self-administered closed-ended questionnaire. Statistical Package for the Social Sciences (SPSS V.16) was used for statistical analysis. Kruskal-Wallis test and Mann-Whitney U-test were used to assess differences in dental anxiety between student groups. The level of significance was considered to be P < 0.05. Results: There were about 69% women and 31% men with the mean age of 21.01 ± 2.91 years. Senior dental students showed a significantly lower dental anxiety than pharmacy ( P < 0.001) and dental students in the early years ( P < 0.001). Women reported significantly higher dental anxiety than men ( P = 0.001). Dental anxiety was also associated with having no prior dental experience ( P < 0.001). The most fearful situation reported by the participants was local anesthetic injection. Conclusions: Dental anxiety was significantly associated with sex, level of study, and the past dental experience. Dental education and awareness might be a significant factor in reducing dental anxiety.